JOB SATISFACTION AND TURNOVER INTENTION OF BLUD WORKERS AT TROSOBO PUBLIC PRIMARY HEALTH CARE - Budiningsih, Annisa Tria; Ernawaty, Ernawaty (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Job satisfaction is defined as a person's attitude or emotional response toward their job duties. Poor job satisfaction leads to turnover. Trosobo public primary health care staffing data showed a high turnover intention of BLUD workers. This study aims to determine the job satisfaction and turnover intention of BLUD worker at the Trosobo public primary health care. This study was quantitative study with a cross-sectional design. The research was conducted in November 2023 at Trosobo public primary care. Eleven BLUD workers were obtained using total sampling calculations. Data analyzed descriptively. The instruments used in this study were MSQ and TIS-6. The lowest average satisfaction score was recognition (43.64) and the highest were authority and achievement (80,00). Job satisfaction of BLUD workers was in the moderate category (score 26-74) and the turnover intention was in the high category (score >15). Trosobo public primary health care BLUD workers had a moderate category of job satisfaction and high turnover intention. Providing services based on workload and length of service, as well as opportunities for career development to BLUD workers, can be carried out by the Trosobo public primary health care as an effort to reduce the turnover problem